Effect of Particle Size, Density and Shape on Margination of Nanoparticles in Microcirculation - Toy, Randall (2011)
In the recent past, remarkable advances in nanotechnology have generated nanoparticles of different shapes and sizes, which have been shown to exhibit unique properties suitable for biomedical applications such as cancer therapy and imaging. Obviously, all nanoparticles are not made equal. This becomes evident when we consider their transport behavior under blood flow in microcirculation. In this work, we evaluated the effect of critical physical characteristics such as the particle shape, size and density on a nanoparticle’s tendency to marginate towards the vessel walls in microcirculation using an in vitro model. The wall-deposition of nanoparticles was tested in a fibronectin-coated microfluidic channel at a physiologically relevant flow rate. Different classes of nanoparticles (liposome, metal particles) of different sizes (60–130 nm), densities (1–19 g/mL) and shapes (sphere, rod) displayed significantly different deposition as a result of different margination rates. The smaller-sized and the oblate-shaped particles displayed a favorable behavior as indicated by their higher margination rates. Notably, the particle density showed an even more essential role, as it was observed that the lighter particles marginated significantly more. Since nanoparticles must escape the flow in order to approach the vascular bed and subsequently extravascular components for meaningful interactions, the design of nanoparticles strongly affects their margination, a key factor for their ultimate in vivo effectiveness.